[OP.7C.02] PREDICTORS OF ARTERIAL STIFFNESS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (September 2017) - Anyfanti, P.; Triantafyllou, A.; Mantzouranis, E.; Koletsos, N.; Triantafyllou, G.; Chatzimichailidou, S.; Gkaliagkousi, E.; Aslanidis, S.; Douma, S.
Abstract : Objective: Pulse wave velocity (PWV) is a classical marker of arterial stiffness that may be influenced by several anthropometric and hemodynamic factors. Several studies indicate elevated PWV in patients with rheumatoid arthritis (RA), yet few have attempted to identify predictors of impaired PWV in this distinct group of patients. Design and method: Arterial stiffness was estimated among consecutive RA patients attending our Rheumatology Outpatient Unit with measurement of carotid-femoral PWV using applanation tonometry (SphygmoCor). Medical history, anthropometric characteristics and blood pressure (BP) were recorded. Impedance cardiography was applied to evaluate hemodynamic parameters, including systemic vascular resistance index (SVRI); stroke index (SI); cardiac index (CI), and thoracic fluid content index (TFCI). Inflammatory markers and lipid fractions were measured in blood samples. Disease activity and physical function were assessed using the Disease Activity Score in 28 joints (DAS28) and the Health Assessment Questionnaire Disability Index (HAQ-DI), respectively. Results: Among 90 RA patients aged 61.6 ± 11.5 years (females: 77.8%), mean PWV was 8.4 ± 2.2 m/sec and significantly correlated with age (r = 0.636, p < 0.001); systolic (r = 0.637, p < 0.001) and diastolic (r = 0.343, p = 0.001) BP, and body mass index (r = 0.260, p = 0.014), but not with lipid fractions. PWV was higher among males compared to females (9.3 ± 2.1 vs 8.1 ± 2.1 m/sec respectively, p = 0.018), as was in diabetic compared to non-diabetic patients (10.4 ± 2.9 vs 8.3 ± 2.0 m/sec respectively, p = 0.051). Among other hemodynamic parameters, PWV correlated with SVRI (r = 0.402, p < 0.001), SI (r = −0.319, p = 0.002), and CI (r = –0.269, p = 0.010). Of the studied disease-related factors, a positive association was observed between PWV and erythrocyte sedimentation rate (r = 0.284, p = 0.007), C-reactive protein (r = 0.213, p = 0.048), DAS28 (r = 0.206, p = 0.057), as well as HAD-DI (r = 0.290, p = 0.014). Linear regression analysis revealed that age (p = 0.004), systolic BP (p < 0.001), and HAQ-DI score (p = 0.001), independently predicted arterial stiffness, after adjustment for other variables. Conclusions: Apart from increasing age and BP, physical disability appears to be a major determinant of increased arterial stiffness among patients suffering from RA, independently of traditional cardiovascular risk factors and RA characteristics. This association may be evident even in a clinical setting with relatively well controlled patients with rheumatoid arthritis.